The Effectiveness of Islamic Psychotherapy with Zikr Asmaul Husna in Improving the Sleep Quality of Schizophrenic Clients in UPT Rehabilitasi Sosial Bina Laras Kediri - Hafil, Ach. Shodiqil; Sa’adati, Tatik Imadatus; Bagus, Muhamad (Program Studi Psikologi Islam (IAIN) Kediri, 2023)
This study was conducted because there are many schizophrenia survivors, especially those who are undergoing the rehabilitation process at the UPT Rehabilitasi Sosial Bina Laras (RSBL) Kediri. Schizophrenia is a serious psychiatric disorder, in which the individual experiencing it loses self-control. This loss of self-control disrupts the sleep cycle which is a necessity in human life. Therefore, researchers tried to conduct experiments on schizophrenic clients at UPT Rehabilitasi Sosial Bina Laras Kediri to improve sleep quality by applying zikr asmaul husna as one of the methods in Islamic Psychotherapy. The purpose of this study was to determine the effect and effectiveness of remembrance of asmaul husna as a psychotherapeutic method in improving the sleep quality of schizophrenic clients in UPT Rehabilitasi Sosial Bina Laras Kediri. This research uses an experimental approach with a quantitative type of research. The research design used was One Group Pretest-Posttest Design. The study sample consisted of 10 schizophrenia clients. Data in this study were collected through questionnaires and observations. The results of the analysis using the Paired Samples Statistics test showed that the average value of the pretest was 8.90, while the post-test value was 9.00. There is a change in value between pretest and posttest. However, the test results using the Paired Samples T-Tests test showed that Sig (2-Tailed) > 0.05, which is 0.899 > 0.05. Thus, it can be concluded that there is no significant difference in the filling of the questionnaire. Although there was no significant difference in filling out the questionnaire, there were differences in scores before the application of the method (pretest) and after application (posttest). Calculations using linear regression show that the value of R Square is 0.370 or 37.0%. From this figure, it can be concluded that the effectiveness of remembrance asmaul husna as an Islamic Psychotherapy method in improving the sleep quality of schizophrenic clients in UPT Social Rehabilitation Bina Laras Kediri by 37.0%, while the remaining 63.0% is influenced by other factors that are not reviewed.